PENGARUH PENGAJIAN RUTIN PUSAT PASIH TERHADAP PENINGKATAN IBADAH MAHASISWA PENGHUNI ASRAMA STAIN PAREPARE MAHASISWA PROGRAM PASIH - HALIDIN, ALI; MARHANI, HJ. MARHANI (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
The main learning target in central PASIH for akademik years 2010 - 2013 is the reading of the book of pure Islam or commonly called yellow book written by scholars of the Salaf Islam spread through the world. It is intended to remember, that many scholars who have died and have no replacements again to continue their propaganda and scientifc treasures.The problem studied are; How is the implementation of a routine recitation Pasih Center STAIN Parepare?; How is the quality of student dormitories worship center Pare ParePasihSTAIN ?; How do the routine recitation Pasih center STAIN Pare Pare ?. The purpose of this research is based on problems that have been studied.The conclusion in this study is a socio-religious groups such as the study has a major role in the formation of the integrity of its members among the members of the group, also has a major role in shaping the character of worship group members. Center for their routine Pasih STAIN Pare Pare great inï¬uence in raising the level of student worship, especially boarder daughter